Who Cares for You at Home? Personal and Household Services in Europe - Annette Angermann; Werner Eichhorst (Institute for the Study of Labor (IZA), 2013)
Personal and household services have grown in importance as a potential area of employment creation. By formalizing personal and household services, not only can service jobs be created with providers, but also private households can be relieved from informal work in order that women in particular can participate more strongly in the labor market. This paper reviews the findings from national experiences with strategies to develop formal personal and household services in European countries, addressing issues such as the definition of these services, quality and professionalization, organizational infrastructure, public support schemes and working conditions. We argue that, under certain institutional conditions, personal and household services can represent an important area of regular employment and increase the reconciliation of work and family life.
Keywords: J14; J38; J45; 330; personal and household services; Europe; voucher systems; care